"Lemak siapa? bukan saya! let's show the fat and us are not compatible: a health promotion program - Abdull Rahim, Mohd Hafiez; Ahmad Saman, Mohd Shahril; Selamat, Mohamad Ikhsan; Xin Wee, Chen (Faculty of Medicine, 2024)
Obesity remains one of the most pressing public health challenges in Malaysia, with a national prevalence of 21.8% in 2023, reflecting an alarming 10% increase since 2011, according to the NHMS 2023. In response to this concern, a health promotion program, “Jauhi Obesiti,” was organised. Spearheaded by Year 4 MBBS students (Group 4) under the supervision of the Public Health Medicine Department, UiTM.